Power-gating in a multi-core system without operating system intervention - WILLIAMS SCOTT ALAN; LONGNECKER MATTHEW RAYMOND; DUMPA VENKATA KRISHNA REDDY; AHMAD SAGHEER; BIGNELL ROBERT ALAN (2015)
To preserve power and increase the overall efficiency of the CPU, the platform idle driver causes the power gate controller to cut power to the idle core. Such power gating is autonomous, i.e., the operating system and the other cores are not involved. In operation, the platform idle driver first prepares the core and the power gate controller for power gating the core. The platform idle driver then triggers the power gating. The power gate controller monitors interrupts released by the interrupt controller, and if any on the released interrupts are associated with the power gated core, the power gate controller resumes dispersing power to the core.